E-commerce web site evaluation : developing a framework and method for the systematic evaluation of e-commerce web sites and using correspondence analysis to represent the results graphically per industry - Van der Merwe, Rian (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEng) -- Stellenbosch University, 2001.